Improvement of the Institution of Rehabilitation and Compensation for Harm Caused by Illegal Actions of the Body Conducting the Criminal Procedure - SASSIN, Alexandr Gennadievich (Journal of Advanced Research in Law and Economics, 2019)
The policy of Kazakhstan is aimed at ensuring the real access of citizens to justice and reducing the unjustified use of coercive measures associated with the invasion in the rights and legitimate interests of an individual protected by the Constitution of the country. It is important not only to protect the citizens’ constitutional rights and freedoms from criminal attacks, to expose and punish those who commit crimes but also to prevent violations of their constitutional rights and freedoms by those state bodies that are meant to protect their rights and legitimate interests. Criminal procedural legislation must ensure that all participants in criminal procedure securely exercise their rights while simultaneously imposing relevant responsibilities on bodies conducting the criminal procedure. Only in this case, it is possible to fulfill the tasks of criminal procedure. There is an urgent need for a comprehensive in-depth study and synthesis of the results of the judicial-administrative reforms carried out in Kazakhstan, determining the degree of their effectiveness and adequacy to the real needs of the society and state, as well as the degree of their implementation in sectoral and other legislation.